Kerawang Postal Notification System (KPNS) / Khairun Atikah Nisa Azman - Azman, Khairun Atikah Nisa (2017)
Nowadays, it is a common to use an information system as an everyday organization operation; there is plenty of information system which is commonly used including notification system. Notification system can be defined as a platform to deliver message to a small or large group of people. This project describes about Kerawang Postal Notification System (KPNS) that is developed to inform students on the arriving of their parcels. Currently, the college informed students manually by using paper that shows the student name and the arrival date which will be paste on the board in front of the college office. By using this current practice, student inclined to overlook their name on the board. Therefore, the development of this system acts as an alternative to improve the process of notifying students using an online system compare to using a manual processes. Rapid Application Development (RAD) Model is used as a project methodology to develop KPNS. This system has been evaluated by 30 users and the results are based on the system interface with 3.73 (SD=0.52), the effectiveness of the system with mean 3.83 (SD=0.70), ease of use of the system with mean of 3.90 (SD=0.61), the system usability with mean 3.87 (SD=0.57), efficiency of the system with mean of 4.10 (SD=0.48) and learn ability of the system with mean 3.53 (SD=0.68). The recommendations of future enhancement of KPNS include transforming this web based application to mobile application and use a bar scanning code application.